2021
DOI: 10.1016/j.celrep.2021.109819
|View full text |Cite
|
Sign up to set email alerts
|

USP7 and VCPFAF1 define the SUMO/Ubiquitin landscape at the DNA replication fork

Abstract: Highlights d VCP and USP7 control the SUMO/ubiquitin landscape during DNA replication d VCP is recruited by FAF1 to chromatin-associated SUMO/ ubiquitylated proteins d FAF1 recognizes both SUMO and ubiquitin on target proteins d The control of DNA replication by VCP FAF1 and USP7 is evolutionarily conserved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…The evolution of Ubxn7 to specifically link neddylated cullins with their substrates and the processing factor p97 is an additional level of regulation that ensures efficiency in p97 substrate targeting. The role of UBXN-3 in regulating SUMOylated factors at replication forks seems to have been conserved throughout evolution as it is also the case in human immortalized cells (29). It will be very interesting to decipher the contribution of FAF1 and UBXD7 to replisome disassembly in human cells in the future.…”
Section: Ubxn7 and Faf1 During Replicationmentioning
confidence: 92%
See 1 more Smart Citation
“…The evolution of Ubxn7 to specifically link neddylated cullins with their substrates and the processing factor p97 is an additional level of regulation that ensures efficiency in p97 substrate targeting. The role of UBXN-3 in regulating SUMOylated factors at replication forks seems to have been conserved throughout evolution as it is also the case in human immortalized cells (29). It will be very interesting to decipher the contribution of FAF1 and UBXD7 to replisome disassembly in human cells in the future.…”
Section: Ubxn7 and Faf1 During Replicationmentioning
confidence: 92%
“…Immunodepletion of Ubxn7, but not Faf1, from egg extract leads to a delay in replisome disassembly (Figures 2 and 3). The C. elegans homologue of Faf1, UBXN-3, has been shown to be important for CMG helicase unloading by p97 in S-phase and in mitosis (4,11), but also to regulate other replication factors such as CDT-1 and, recently, to regulate SUMOylated factors at DNA replication forks (17,28,29). It is clear, therefore, that UBXN-3 plays a key role in extraction of proteins from chromatin during DNA replication in C. elegans embryos.…”
Section: Ubxn7 and Faf1 During Replicationmentioning
confidence: 99%
“…An emerging question is how cells would decide between RNF4 mediated degradation and TRIM25 signaling pathways. One exciting candidate could be USP7, a SUMO-targeted ubiquitin protease that cooperates with VCP to define SUMO/ubiquitin levels at replication forks 50, 54 . In support, USP7 has been found to interact with TRIM25 55 , and has a clear preference for cleavage of K48- over K63-linked chains 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Then, poly-sumoylated EME1 is extracted by the AAA ATPase VCP/p97-NPL4-UFD1 complex, which we observed in our EME1-IP (Extended Data Fig. 7) and which is established to extract poly-sumoylated and/or ubiquitinated proteins form replication forks and nucleolar repair condensates [49][50][51][52] . This step likely requires poly-sumoylation-dependent ubiquitination, as it best understood for the STUbL RNF4 but may also apply to TRIM25.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SPRTN can be recruited along with p97 to SUMO-conjugated TOP1-DPCs via the p97 co-factor TEX264, which associates with replication fork presumably tethering SPRTN to DPCs that block ongoing DNA replication ( Fielden et al, 2020 ) ( Figure 1G ). However, the stimulatory function of SUMO on SPRTN activity has yet to be confirmed in vitro , and could be caused by indirect effects due to the global role of SUMOylation on DNA replication ( Lecona et al, 2016 ; Franz et al, 2021 ). In contrast to SPRTN, which is expressed in different cell types, ACRC (GCNA) is mainly expressed in germ cells ( Carmell et al, 2016 ) where it was recently shown to target TOP2-DPCs during meiosis ( Bhargava et al, 2020 ; Dokshin et al, 2020 ) ( Figure 1G ).…”
Section: Role Of Sumo In Dna-protein Crosslink Removal By Dna-protein...mentioning
confidence: 99%